2018
DOI: 10.1002/aoc.4248
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Ni‐Modified Graphene Oxide Complex as an Efficient Catalyst for the Synthesis of Sulfides via Reaction of Arylhalides with S8 or Thiourea

Abstract: In this work, complex of Ni-modified graphene oxide was prepared and characterized using FT-IR spectroscopy, SEM, XRD, TGA and ICP-OES techniques. This compound used as an efficient and recoverable catalyst for the C-S coupling reaction using sulfur-transfer reagents (S 8 or thiourea). The catalyst was easily separated using a simple filtration and reusable without significant loss of their catalytic efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…[5][6][7] When the size of particles is decreased, their surface area is increased, which will be lead to high capacity of catalyst loading. [1][2][3][4][5][6][7][8] For example, iron oxide, [9] mesoporous silica materials, [10] carbon nanotubes, [11] ionic liquids, [12] polymers, [13] graphene oxide, [14,15] heteropolyacids, [16] boehmite nanoparticles, [17] etc., have been used as catalyst supports; however, all of these materials require chemical procedures and chemical starting materials for their preparation which are expensive and not environmentally friendly. [1][2][3][4][5][6][7][8] For example, iron oxide, [9] mesoporous silica materials, [10] carbon nanotubes, [11] ionic liquids, [12] polymers, [13] graphene oxide, [14,15] heteropolyacids, [16] boehmite nanoparticles, [17] etc., have been used as catalyst supports; however, all of these materials require chemical procedures and chemical starting materials for their preparation which are expensive and not environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] When the size of particles is decreased, their surface area is increased, which will be lead to high capacity of catalyst loading. [1][2][3][4][5][6][7][8] For example, iron oxide, [9] mesoporous silica materials, [10] carbon nanotubes, [11] ionic liquids, [12] polymers, [13] graphene oxide, [14,15] heteropolyacids, [16] boehmite nanoparticles, [17] etc., have been used as catalyst supports; however, all of these materials require chemical procedures and chemical starting materials for their preparation which are expensive and not environmentally friendly. [1][2][3][4][5][6][7][8] For example, iron oxide, [9] mesoporous silica materials, [10] carbon nanotubes, [11] ionic liquids, [12] polymers, [13] graphene oxide, [14,15] heteropolyacids, [16] boehmite nanoparticles, [17] etc., have been used as catalyst supports; however, all of these materials require chemical procedures and chemical starting materials for their preparation which are expensive and not environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxide was prepared from graphite powders using modied Hummers' method. 21 In this regard, concentrated sulfuric acid (23 mL) was added slowly to a mixture of graphite powder (1 g) and NaNO 3 (0.5 g), and it was then stirred in an ice bath for 15 min. Then, potassium permanganate (3 g) was slowly added to the stirred mixture and again allowed to stir for 1.5 h at 0 C. Then, the mixture was stirred for 2 h at 35 C. Aer this, deionized water (46 mL) was slowly added under stirring and the solution temperature was stirred at 98 C for 30 min.…”
Section: Synthesis Of Graphene Oxidementioning
confidence: 99%
“…48,49 The second weight loss, which is about 18%, is observed between 100 and 250 C, which is attributed to the decomposition of thermally less stable and labile oxygencontaining functional groups (hydroxyl, epoxy, and carboxylic acid). 21,50 The third weight loss at about 300 C corresponds to the more stable oxygen-containing functionalities and the bulk pyrolysis of the carbon skeleton. 51,52 The fourth weight loss, which shows a major decrease in the mass of about 31% in the temperature range of 250-450 C, is attributed to the decomposition of supported organic moieties and the copper complex on the surface if GO-Ni MNPs, 21,31 which can be possibly related to the strong chemical interaction between GO-Ni MNPs and the organic groups.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghafouri‐Nejad et al [ 137 ] demonstrated the use of Ni‐modified GO as a highly efficient and recoverable catalyst for C‐S coupling reaction. A mixture of aryl halide and thiourea/S 8 with NaOEt in the presence of Ni(II)‐modified‐GO as a catalyst and DMSO as a solvent at 120°C for 30 min was studied.…”
Section: Go‐supported Metals As Catalystmentioning
confidence: 99%